Changes in serum uric acid levels as a predictor of future decline in renal function in older adults with type 2 diabetes. Issue 40 (8th October 2021) - Shibata, Yusuke; Yamazaki, Masanori; Kitahara, Junichiro; Okubo, Yosuke; Oiwa, Ako; Sato, Ai; Komatsu, Mitsuhisa
Abstract : Abstract: Given that factors affecting renal function remain unknown, this study aimed to identify key predictors of estimated glomerular filtration rate (eGFR) deterioration, which is a representative of renal function decline in older adults with type 2 diabetes (T2DM). In an exploratory prospective observational study, we enrolled 268 Japanese people with T2DM aged ≥20 years who were followed up at Shinshu University Hospital. Among those, 112 eligible individuals aged ≥65 years were included in the present study. Factors associated with 3-year changes in eGFR (ΔeGFR) and eGFR deterioration (ΔeGFR < 0) were identified using bivariate and multivariable analyses. Regarding baseline values of the subjects, the mean age was 73.5 years, mean blood pressure was 131/74 mm Hg, mean hemoglobin A1c was 7.1%, mean eGFR was 62.0 mL/min/1.73 m 2, mean urinary albumin excretion was 222.6 mg/gCre, and mean serum uric acid (UA) was 5.5 mg/mL. In bivariate analysis, the 3-year change in UA (ΔUA) levels was significantly correlated with ΔeGFR (r = −0.491, P  < .001), but the baseline UA was not (r = 0.073, P  = .444). Multiple linear regression analysis revealed that ΔUA was a significant negative predictor of ΔeGFR in the model that included sex, age, body mass index, serum albumin, and ΔUA as explanatory variables. Moreover, multiple logistic regression analysis demonstrated that ΔUA had a positive association with ΔeGFR <0 (odds ratio 2.374; 95% confidence interval 1.294–4.357). Thus, future renal function decline can be predicted by ΔUA but not by baseline UA in older adults with T2DM. Further research is needed to determine whether lowering the serum UA level can prevent eGFR decline. Abstract : Supplemental Digital Content is available in the text